PEMANFAATAN Spirulina platensis UNTUK MENINGKATKAN KINERJA PERTUMBUHAN DAN KETAHANAN TUBUH IKAN ZEBRA (Danio rerio) - Lukman Anugrah Agung; Muh. Herjayanto; Eltis Panca Ningsih; Edo Ahmad Solahudin; Esa Rama Widiyawan (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2021)
The purpose of this research is to evaluate the effect of different concentration of Spirulina platensis supplementation on artificial feed for zebrafish (Danio rerio) to increase growth performance and immunity from environmental pressure. The experimental research was carried out from October until November 2020. The purpose of this research is to evaluate the effect of S. platensis different concentration supplementation on artificial feed for zebrafish (Danio rerio) to increase growth performance and immunity from environmental pressure. The experimental research was carried out from October 2020 until November 2020 at Aquaculture Laboratory, Universitas Sultan Ageng Tirtayasa, Serang, Banten. This research used a complete randomized design (CRD) consisted of 4 treatments and 3 replications. Control was commercial pellet which no S. platensis enriched (A), pellet enriched with 3% of S.platensis (B), pellet enriched with 6% of  S. platensis(C), and last treatment were pellet enriched with 9% of  S.platensis (D). The results showed that treatment C was the best dosage of S. platensis for zebrafish rearing for 40 days both growth and immunity performance. Absolute length, Specific growth rate of length, Absolute weight, Specific growth rate of weight were significantly different, but survival rate were not significantly different which were 0.646±0.112g, 0.714±0.10g, 0.102±0.020%, 1.422±0.215%, 100% respectively. Immunity performance was shown by the stress test at low pH. It was also significantly different when exposed to pH at 5 ppt among the treatment. Treatment C was the highest survival rate which was 63.33±5.77% after stress test at low pH.